Pemberdayaan Peternak Kambing Senduro melalui Integrated Farming di Kelompok Ternak Mekar Sari, Kecamatan Senduro, Lumajang - Lilik Maslachah; Widya Paramita Lokapirnasari; Yossy Imam Candika; Emy Koestanti Sabdoningrum; Rahma Kurnijasanti (Institut Pertanian Bogor, 2025)
Senduro goat has been designated as a valuable genetic resource of Indonesia’s local livestock that must be protected and preserved. The Senduro goat, which thrives in Senduro Subdistrict, holds great potential as an economic driver for the village and therefore needs to be continuously developed and maintained. This community service program was carried out to address the issues faced by the partner farmers of the Mekar Sari Livestock Group through technology-based community empowerment. The main goal of this activity is to enhance community self-reliance and welfare through a Science Techno Park approach, which includes the application of technology in integrated farm development, improving farmers' skills in ruminant feed management, processing manure waste into fertilizer, and conducting livestock business analysis, including business and financial planning. The activities were carried out in several stages, namely: communication and coordination with relevant parties, observation and partner site survey, workshops, field practice through demo plots, and evaluation and monitoring. The evaluation was conducted using pre-test, post-tests and questionnaires to assess the improvement in partner knowledge. The evaluation results showed that, in general, the partners found the activity very beneficial, engaging, and capable of increasing goat farmers’ knowledge about the integrated farm concept using a zero-waste approach. The partners' understanding of feed processing, waste management, and business analysis significantly increased from 52 to 92%. This activity received a positive response from the Mekar Sari Goat Farmer Group in Senduro, Lumajang. The sustainability of this program is further coordinated with the relevant government agencies in Lumajang Regency to support the development of sustainable livestock farming in the region.